دور السياحة في تحسين واقع المرأة الريفية - هرمز, نور الدين; أبازيد, ثناء; اسبر, ميساء (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يتناول البحث واقع المرأة الريفية والصعوبات التي تعانيها من ضعف في مستوى الدخل والتمكين الاقتصادي والاجتماعي والنفسي، ومفهوم السياحة الريفية. ومن ثم يتناول البحث أثر السياحة الريفية على المرأة من خلال مساهمتها في تخفيض معدلات الفقر وخلق فرص العمل، ومن ثم دور السياحة الريفية في تمكين المرأة الريفية الاجتماعي والنفسي، وأدوات تفعيل دور السياحة في تمكين المرأة. وقد توصلت الباحثة من خلال التحليل النظري والاختبار الإحصائي لبيانات العينة القصدية المستهدفة إلى نتائج تدعم صحة فرضيات البحث بأن للسياحة دور هام في تحسين واقع المرأة الريفية. This research deals the rural woman's condition and the difficulties she experiences economically, socially and psychologically. It shows how rural tourism can alleviate hardships. In particular, the research examines the impact of tourism on rural women through its contribution to reduction of poverty and job creation. Rural tourism has an empowering effect socially and psychologically. Theoretical analysis and statistical test of the data of studied sample support the validity of the hypothesis of this research that tourism has an important role in improving the situation of rural women